Pengaruh Penataan Lahan Hijau sebagai Bagian dari Perancangan Arsitektur terhadap Perkembangan Emosi Masyarakat - Marina, Nurul Fitria; Brilliana, Aisyah; Akifah, Salsa Bila Nur (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This article discusses the influence of green space planning in architectural design on the emotional development of the community in Surabaya. With an increasing population and demand for urban facilities, Surabaya faces challenges such as traffic congestion and a reduction in green space. This study examines how green open spaces can contribute to the emotional well-being of the community, with reference to a case study in Seoul, South Korea. The method used is qualitative analysis of secondary data. This study found that green open spaces in CheongyeCheong have an impact on emotional development, the economic level of the community, and the surrounding environment.